PROPOSED BUSINESS STRATEGY FOR AYA KOPI COFFEE SHOP (CASE STUDY IN AYA KOPI) - Adimaz Fernando, Moh
Aya Kopi is one of the coffee shops in the city of Bandung. Aya Kopi was founded by Adi Putra, Tomy Adrian, and Alfan Nurahman. It started from their hobby who likes to brew and enjoy a cup of coffee. Coffee types are provided at Aya Kopi is Arabica single origin and Robusta. Aya Kopi coffee product is espresso-based, and manual brew coffee. The problem faced by this company is that Aya Kopi coffee shop is difficult to compete with competitors so that sales targets are not achieved. The main cause identified from several existing problems is that Aya Kopi is facing strong competition in the coffee shop industry. This indicates that Aya Kopi coffee shops should not remain stagnant in the market because with new coffee shops open every day, existing coffee shops on the market must be able to evolve with changes in the industry.Coffee shop owner need to know and learn about the strengths, weaknesses, threats, and opportunities they have to produce a strategy that suits their conditions. This research produced the business strategy for Aya Kopi issues. This study used internal analysis; resources, capabilities, value chain, and external analysis; general analysis, industry environment, competitor analysis. Root cause analysis was created to know all the problem faced. Identified root cause of some issue that Aya Kopi faces the strong force of competitive rivalry or competition in the food service and coffee Shop industries. There are several factors that cause it like; large number of firms in the industries, low levels of product differentiation in coffee shops industry. The presence of many competitors in this industry can cause a high bargaining power from the customer.Customers can compare products offered between one coffee shop and another. Customers can choose products and services that suit their needs. This is also due to the lack of promotion and not maintaining social media from Aya Kopi for social engagement to customers. Lack of parking area and unavailability of ordering facilities through applications such as Go-Food or Grabfood make customers have limitations to buy products from Aya Kopi. From internal and external analysis that has been done, Aya Kopi SWOT can be identified. The next stage uses the Internal-External Matrix (IE) to analyze the division's current position and suggest strategies for the future and TOWS matrix analysis to formulate alternative strategies. Based on the Internal-External (IE) matrix, the product development strategy was chosen to be applied at the Aya Kopi coffee shop. The results of the TOWS Matrix Analysis identify seven alternative strategies that can be implemented. Alternative strategies that have been produced will be selected strategies that are suitable with the current condition of Aya Kopi coffee shop. Some alternative strategies chosen are developing seasonal products, creating collaboration events with communities, optimizing social media for social engagement, and open online distribution channels. The formulated strategy is expected to be the solution to the problem.